Solitaire™ with the Intention for Thrombectomy as Primary Endovascular Treatment for Acute Ischemic Stroke (SWIFT PRIME) Trial: Protocol for a Randomized, Controlled, Multicenter Study Comparing the Solitaire Revascularization Device with IV tPA with IV tPA Alone in Acute Ischemic Stroke. Issue 3 (April 2015) - Saver, Jeffrey L.; Goyal, Mayank; Bonafe, Alain; Diener, Hans-Christoph; Levy, Elad I.; Pereira, Vitor M.; Albers, Gregory W.; Cognard, Christophe; Cohen, David J.; Hacke, Werner; Jansen, Olav; Jovin, Tudor G.; et al.
Rationale: Early reperfusion in patients experiencing acute ischemic stroke is critical, especially for patients with large vessel occlusion who have poor prognosis without revascularization. Solitaire™ stent retriever devices have been shown to immediately restore vascular perfusion safely, rapidly, and effectively in acute ischemic stroke patients with large vessel occlusions. Aim: The aim of the study was to demonstrate that, among patients with large vessel, anterior circulation occlusion who have received intravenous tissue plasminogen activator, treatment with Solitaire revascularization devices reduces degree of disability 3 months post stroke. Design: The study is a global multicenter, two-arm, prospective, randomized, open, blinded end-point trial comparing functional outcomes in acute ischemic stroke patients who are treated with either intravenous tissue plasminogen activator alone or intravenous tissue plasminogen activator in combination with the Solitaire device. Up to 833 patients will be enrolled. Procedures: Patients who have received intravenous tissue plasminogen activator are randomized to either continue with intravenous tissue plasminogen activator alone or additionally proceed to neurothrombectomy using the Solitaire device within six-hours of symptom onset. Study Outcomes: The primary end-point is 90-day global disability, assessed with the modified Rankin Scale (mRS). Secondary outcomes include mortality at 90 days, functional independence (mRS ≤ 2) at 90 days, change in National Institutes of Health Stroke Scale at 27 h, reperfusion at 27 h, and thrombolysis in cerebral infarction 2b/3 flow at the end of the procedure. Analysis: Statistical analysis will be conducted using simultaneous success criteria on the overall distribution of modified Rankin Scale (Rankin shift) and proportions of subjects achieving functional independence (mRS 0–2).